Effect of amino acid substitutions in a potential metal-binding site of AnfA on expression from the anfH promoter in Azotobacter vinelandii. - Premakumar, R (1994)
AnfA, an activator required for transcription of the structural genes encoding nitrogenase 3 (anfHDGK) in Azotobacter vinelandii, has a potential metal-binding site [(S19)H(C21)FTGE(C26)R] in its N terminus. Growth studies and expression of an anfH-lacZ fusion in mutants containing amino acid substitutions in this site indicate that Ser-19 is not required for AnfA activity whereas Cys-21 and Cys-26 are required. Residual expression of the anfH-lacZ fusion in AnfA- mutants was found to be due to activation by VnfA, the activator required for expression of genes encoding nitrogenase 2.